Focused Ultrasound Preconditioning for Augmented Nanoparticle Penetration and Efficacy in the Central Nervous System. Issue 49 (22nd October 2019) - Mead, Brian P.; Curley, Colleen T.; Kim, Namho; Negron, Karina; Garrison, William J.; Song, Ji; Rao, Divya; Miller, G. Wilson; Mandell, James W.; Purow, Benjamin W.; Suk, Jung Soo; Hanes, Justin; et al.
Abstract: Microbubble activation with focused ultrasound (FUS) facilitates the noninvasive and spatially‐targeted delivery of systemically administered therapeutics across the blood–brain barrier (BBB). FUS also augments the penetration of nanoscale therapeutics through brain tissue; however, this secondary effect has not been leveraged. Here, 1 MHz FUS sequences that increase the volume of transfected brain tissue after convection‐enhanced delivery of gene‐vector "brain‐penetrating" nanoparticles were first identified. Next, FUS preconditioning is applied prior to trans‐BBB nanoparticle delivery, yielding up to a fivefold increase in subsequent transgene expression. Magnetic resonance imaging (MRI) analyses of tissue temperature and K trans confirm that augmented transfection occurs through modulation of parenchymal tissue with FUS. FUS preconditioning represents a simple and effective strategy for markedly improving the efficacy of gene vector nanoparticles in the central nervous system. Abstract : Advanced pulsed focused ultrasound "preconditioning" schemes for amplifying the dispersion and efficacy of non‐viral brain‐penetrating nanoparticle formulations that are delivered across the blood–brain barrier are described. The powerful focused ultrasound preconditioning strategy presented here may be appended to already‐established protocols to markedly augment the efficacy of nonviral gene therapy strategies in the central nervous system.